A influência da oferta dos serviços de saúde e educação superior na Região Geográfica Intermediária de Rondonópolis-MT - Pereira, Paulo Sérgio (2018)
The city of Rondonópolis, starting from its integration into the national productive process, especially in the agroindustrial sector, started from the 1970s, began to impress a remarkable importance in the regional context of southern Mato Grosso state. The socio-spatial transformations experienced in the different scales, in the period when the twentieth century and the beginning of the XXI century, in a certain way, represented potential elements in the consolidation of the city of Rondonópolis as the main point of articulation of the urban network of the southern region of the state. It is in this scenario that the research sought to highlight the actors and their respective actions, in order to unveil through the health services and higher education the influence exerted by the city in the context of the Intermediate Geographical Region of Rondonópolis, this region, composed of eighteen municipalities, which tend to constitute their relations, be they intense or superficial, are these induced, as is the case of the regionalization of health imposed by the Unified Health System – SUS, or those that are spontaneously constituted, such as, for example, when the city becomes the only alternative or the most viable in the search for certain services, among them, those of health and higher education. Methodologically, the research opted for the analysis of hospitalization data from three public hospitals; Santa Casa de Rondonópolis, Sister Elza Giovanella and House of Health and Psychosocial Support Center – CAPs Paulo de Tarso in the period from 2013 to 2017 from the Information System Hospital Information – SIH of the SUS, in addition to specialized services of nephrology health, in the Clinics Nephrology Center of Rondonópolis and Pronefron Clinical Nephrology and Renal Replacement Therapy, in addition to the specialized service in oncology, through the chemotherapy procedure, performed at the Nucleus of Specialized Oncology Therapy of Rondonópolis – NUTEC. In order to demonstrate the centrality from the higher education service, the research was directed to the analysis of the origin of the students in the Campus of the Federal University of Mato Grosso – UFMT of the Campus of Rondonópolis – CUR from 2013 to 2018, in addition to seeking information from origin of students enrolled in 2018, at the two campuses of the University of Cuiabá – UNIC of Rondonópolis. In order to discuss the efficacy or not of the regional basic education schools in filling the vacancies in the courses of the Federal University of Mato Grosso – UFMT in the University Campus of Rondonópolis – CUR, it was tried to analyze comparatively the origin of the new students in different periods, aiming at as well as the construction of arguments that can give answers or raise debates around the new forms of selection implemented from the National High School Examination (ENEM) and the Unified Selection System (SISU). The results showed that the health and higher education services contribute in a singular way to evidence the centrality exercised by the city of Rondonópolis in the Intermediate Geographical Region, because, despite the city having a varied service sector, besides responding quantitatively and qualitatively to the demands of the agroindustrial sector, also having a wide and varied commerce, it is through these services that the daily or pendular mobility materializes, consolidating its leadership role in the hierarchy of the urban centers of the numerous municipalities that compose the southern portion of the state of Mato Grosso.